The AIIMS Bhopal Pre-sternal Keloid Scale (ABPSKS): A Method for Evaluating the Incidence of Severity and Evading Comparisons in Treatment Results - Ihsanullah Khan, Majid Hussain, Muhammad Shahid Farooq, Asadullah Awan, Masroor Ahmad Baloch, Naveed Ahmad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There are numerous ways in which pre-sternal keloids differ from keloids that develop elsewhere, including in their pathophysiology, clinical manifestations, and treatment. Objective: Aim was to determine the effectiveness of AIIMS Bhopal Pre-sternal Keloid Scale (ABPSKS) for assessing severity among cases of pre-sternal keloid. Methods: This prospective study was conducted at Burns and Plastic Surgery Center Hayatabad, Peshawar during September 2022 to May 2023. Total 137 patients of both genders were presented in this study. All the patients had symptoms of pre-sternal keloid were included. Comprehensive demographic data was gathered following the acquisition of informed written consent. AIIMS Bhopal Pre-sternal Keloid Scale (ABPSKS) was employed among all cases. SPSS 22.0 was used to analyze all data. Results We found among all, 73 (53.3%) were males and 64 (46.7%) were females. The patients mean age 23.6 years. There were 57 (41.6%) married patients. Most common symptoms among cases were itching, pain and skin infection. Trauma and burns were the main common causes. We found severity of disease among 115 (83.9%) cases. Efficacy of disease location was found in 110 cases which is higher as compared to observer found in 80 cases with p value <0.005. Conclusion: We concluded in this study that ABPSKS is an effective tool for assessing disease severity and location among cases of pre-sternal Keloid. Keywords: ABPSKS, pre-sternal keloid, severity, location